No sex differences in fatigability or neuromuscular responses during one set of maximal intended velocity muscle actions to failure at 30 % one-repetition maximum - Tyler J. Neltner; Robert W. Smith; Jocelyn E. Arnett; Dolores G. Ortega; Richard J. Schmidt; Dona McCanlies; Terry J. Housh (Current Research in Physiology)
Traditionally, research using dynamic constant external resistance (DCER) training has focused on self-selected velocities. This study aimed to examine sex differences in fatigability and neuromuscular responses during maximal intended velocity, DCER forearm flexion muscle actions to failure. Fourteen men (mean ± SD; age: 22.9 ± 2.0 yrs) and 13 women (age: 22.9 ± 2.6 yrs) completed one set of forearm flexion muscle actions to failure performing the concentric phase of the repetition at maximal intended velocity (as fast as possible). Electromyographic (EMG) and mechanomyographic (MMG) signals were recorded from the biceps brachii. The results indicated that men were significantly stronger and more powerful than women, however, there were no sex differences in the number of repetitions to failure (70 ± 18) or reductions in peak force (31 ± 8 %), peak velocity (57 ± 18 %), or peak power (64 ± 17 %). Additionally, there were no sex differences in the neuromuscular responses, which included increases in EMG amplitude (AMP), decreases in EMG mean power frequency (MPF), and no changes in MMG AMP or MPF. The increase in EMG AMP and decrease in EMG MPF, combined with no changes in MMG AMP or MPF, suggested that the decreases in performance were due to excitation contraction coupling failure, rather than a reduction in central drive. Thus, despite the low relative load, the maximal intended velocity muscle actions resulted in similar impairments of contractile function for the men and women that diminished sex differences in fatigability.